Gastric outlet obstruction secondary to peritoneal drain placement for necrotizing enterocolitis in a premature infant - Georgia M. Vasilakis; Dan Parrish (Elsevier, 2021)
Introduction: Gastric outlet obstructions (GOO) are extremely rare outside of congenital conditions. We present a case in which a premature newborn developed a gastric outlet obstruction secondary to peritoneal drain placement for necrotizing enterocolitis (NEC). Case description: A premature infant born with extremely low birth weight was admitted to the NICU. Failed attempts at an orogastric tube placement caused an esophageal perforation and pneumomediastinum which was conservatively managed. The infant developed pneumoperitoneum secondary to necrotizing enterocolitis, indicating surgical management. A Penrose peritoneal drain was placed for abdominal decompression. A gastric outlet obstruction developed, causing concern for gastric volvulus. A bedside exploratory laparotomy was performed to address the gastric outlet obstruction and intestinal perforation. GOO was caused by a kink in the peritoneal drain, which was removed, an ileostomy was created at the site of ileum perforation, and the stomach was decompressed with a gastrostomy tube. Ileostomy was reversed at 6 weeks without complication. Conclusions: Peritoneal drain placement for necrotizing enterocolitis is a well-established treatment alternative to an exploratory laparotomy. Gastric outlet obstruction caused by the drain is a complication that has not been reported. The inability to pass an orogastric tube to decompress the stomach further complicated the case requiring a more invasive approach with a laparotomy.